Design and implementation of a novel user interfacing module for the Cranfield circular toilet. - Noaman, Mohamad Waleed (Cranfield University, 2022)
This thesis presents empirical research on the development and implementation of a novel, water-saving user-interfacing module, that operates as a part of a comprehensive non-sewered sanitation system, the Cranfield Circular Toilet, that performs decentralized human waste evacuation and treatment. Building upon previous knowledge in this project, a prototype was designed, manufactured and assembled. It boasts new automated features that augment the functions of its mechanical evacuation subsystems, utilisation of water for interface flushing from the liquid purification process, and a streamlined design for manufacturability, in preparation for volume production and commercialization. Laboratorial tests were carried out to validate its main functionalities in self- cleaning and waste evacuation of solid and liquid human wastes to the backend treatment modules. Being a first prototype, findings from those tests were substantial in informing future design decisions in the module’s evolution, through selection of suitable and cost-effective operational features, optimisation of its geometric designs, and achieving further rationalisation in using resources, in aim to achieve higher levels of performance and user appeal, and a successful integration with the rest of the sanitation system.
Keywords: water-saving; user-interfacing; non-sewered sanitation system; interface flushing; self-cleaning; integration with sanitation system